Effect of Annealing Temperature on Electrodeposited Iron Oxide Thin Films for Supercapacitor Study (International Journal of Scientific Research in Science and Technology, 2025)
Fe2O3 samples were electrodeposited onto stainless steel at 1.4 V optimum potential using a 0.2 M FeCl3 precursor solution. They were then annealed at various annealing temperatures between 673 and 723 K with 50° increments. XRD analysis verifies that a crystalline rhombohedral crystal structure has formed. A consistent porous, spongy, beautiful gold flower-like morphology is demonstrated by the FESEM and HRTEM morphologies, and wettability tests indicate its hydrophilic nature. The 1 M KOH electrolyte was used for all electrochemical characterizations of the electrodes as they were deposited. The maximal specific capacitance of the optimized electrode is 898.52 Fg-1 at 2 mVs-1 . Using the galvanostatic charge-discharge technique, the highest values of specific energy (SE), specific power (SP), and columbic efficiency (ɳ) were determined to be 45.88 WhKg-1 , 5.33 KWKg-1 , and 97.67%,respectively. According to EIS investigations, the internal resistance was 0.7869 Ώ.